shorebird_subspecies - D'Urban Jackson, Josephine Anne; Dos Remedios, Natalie; Maher, Kathryn H.; Zefania, Sama; Haig, Susan; Oyler-McCance, Sara; Blomqvist, Donald; Burke, Terry A.; Bruford, Mike; Szekely, Tamas; Küpper, Clemens (Dryad Digital Repository, 2017)
This file contains breeding system, breeding range size, subspecies richness and migratory behaviour information for 136 shorebird species. This is the datafile used to test the hypotheses described in the paper using a PGLS approach implemented in R.